Hierarchical scalable storage architecture for massive electronic bill - Fenghua LI; Dingyan LI; Wei JIN; Zhu WANG; Yunchuan GUO; Kui GENG (Tongxin xuebao)
The rise of e-commerce and other network services have greatly promoted the development of electronic bill service,while traditional data storage schemes can no longer satisfy the rapid access requirements of massive electronic bill data.To solve these problems,a hierarchical scalable storage architecture for massive electronic bill was proposed,which combined hash modular algorithm and consistent hash algorithm,and supported fast data locating.A horizontal expansion scheme based on hash modular algorithm was designed to reduce the amount of data that needed to migrate when adding or deleting data nodes.Besides,a data caching scheme based on hot data and a load balancing scheme based on access delay were designed and implemented,further improving the speed of data access.Finally,the experiments prove the effectiveness of proposed architecture and schemes.